Hydro-dissection: An Effective Intra-Operative Technique for Difficult Laparoscopic Cholecystectomies: Hydro-dissection for Difficult Laparoscopic Cholecystectomies - Ali , Aun; Saeed, Summaya; Shahid, Nadia; Ahmed Qureshi, Jabbar; Ahmed, Mohammed; Salam, Ammara (Pakistan Journal of Health Sciences, 2022)
Hydrodissection, a technique used to treat nerve entrapments, involves injecting an anaesthetic, saline, or 5% dextrose in water to separate the nerve from the surrounding tissue. Objectives: To assess the efficacy of this technique in all patients undergoing difficult laparoscopic cholecystectomy in terms of operative time, haemorrhage, and intra-operative complications. Methods: A multicenter observational study was conducted at the department of surgery, PAF Faisal Hospital and Anis Bantva Trust Hospital Karachi. A total of 219 patients were included in this study who underwent laparoscopic cholecystectomy for symptomatic gall stones, with age ranging from 18-70 years, with intra-operative Cuschieri classification >1, using a non-probability sampling method. Results: This study included 219 patients from hospital records categorized as per intra-operative difficulty grading of Cuschieri from grade II-IV. The mean age of patients was 40.46 ±12.50 years, with an average duration of symptoms of 16.95 ± 8.73 days. There were 160 (73.1%) males and 59 (26.9%) females. About two-thirds of patients were admitted through the emergency department. The pre-operative and intraoperative diagnosis of patients was symptomatic cholelithiasis 76 (34.7%), acute on chronic cholecystitis (27.9%), chronic cholecystitis 57 (26.0%), empyema and mucocele gallbladder 11 (5%) each, and Gangrenous gallbladder 3 (1.4%) were recorded. Conclusion: This study showed a clear association of intra-operative complicated anatomy during laparoscopic cholecystectomy to its conversion to open cholecystectomy. Techniques of dissection are of significant importance to minimize injuries to vital structures